Hepatic metabolomics reveals that liver injury increases PCB 126-induced oxidative stress and metabolic dysfunction. (February 2019) - Deng, Pan; Barney, Jazmyne; Petriello, Michael C.; Morris, Andrew J.; Wahlang, Banrida; Hennig, Bernhard
Abstract: The deleterious effects of PCB 126 are complex, and the role of the liver in modifying toxic insult is not well understood. We utilized metabolomics approaches to compare liver metabolites significantly affected by PCB 126 in control mice and a diet induced liver injury mouse model. In this 14-week study, mice were fed either an amino acid supplemented control diet (CD) or a methionine-choline deficient diet (MCD) which promoted nonalcoholic steatohepatitis (NASH) and were subsequently exposed to PCB 126. The liver metabolome was profiled by a global metabolomic analysis using LC-MS. There were clear differences between PCB 126 exposed and control mice in the hepatic metabolomic profiles (216 and 266 metabolites were altered in CD-fed and MCD-fed mice respectively after PCB 126 exposure). PCB 126 modulated glycerophospholipid metabolism, glutathione metabolism, and CoA biosynthesis pathways irrespective of diet; indicating that the disturbance in lipid metabolism and thiol metabolites are general markers of PCB 126 exposure irrespective of liver health. Additionally, metabolites associated with oxidative stress and mitochondrial dysfunction were greatly elevated in PCB 126 exposed mice with compromised livers (e.g., 4-hydroxy-nonenal glutathione, oxylipids, uric acid, and acylcarnitines). Moreover, PCB 126 exposure downregulated redox genes, and the effect was more pronounced in liver injury mice. In conclusion, this study demonstrates that PCB 126 could induce oxidative stress and metabolic dysfunction, and pre-existing liver injury can markedly modify PCB 126-induced metabolic changes. Using metabolic profiling, this study suggests mechanism of enhanced PCB 126 toxicity under liver injury settings. Highlights: Hepatic metabolic profiling of a liver injury mouse model exposed to PCB126. Multiple metabolic pathways were disturbed in PCB 126 exposed mice. ROS related metabolites were elevated in PCB 126 exposed mice with liver injury. PCB126 exposure downregulated redox genes in liver injury mice.